Quality of Work Life of Teaching Staff of A Secondary School In Southern Sonora And Its Effects On The Student Community - Martha Valentina Cantú Muñoz; Celia Yaneth Quiroz Campas; Cecilia Aurora Murillo Félix; Alberto Galván Corral; Carlos Jesús Hinojoza Rodríguez (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study shows the relationship between the quality of work life of the teaching staff of a secondary school in Southern Sonora and its influence on the student community. To determine the existence of the effects of the quality of work life of the teaching staff in the student community of a secondary school in Southern Sonora, and thus generate strategies that support a better comprehensive training of students, the quantitative method was applied in which two instruments were applied in this research. The first was aimed at the teaching staff in which the 41 teachers that make up the total workforce participated and the second which was applied to 227 students. The variables evaluated in the instrument applied to the teaching staff obtained the following results: quality of working life, a mean of 4,021, organizational management, a mean of 4,417 and organizational performance a mean of 4,665. In the instrument applied to the students, results were obtained for the variables under study: quality of student life with a mean of 3,933, student identity with 4,133 and academic performance with a mean of 4,180. Based on the results obtained in the application of the instruments and analysis of results, we can conclude that there is a direct relationship between the quality of work life of the teachers of this school and the impact it causes in the student community.